Functional characterization of maternally accumulated hydrolases in the mature oocytes of the vector Rhodnius prolixus reveals a new protein phosphatase essential for the activation of the yolk mobilization and embryo development - de Almeida, Elisa; Dittz, Uilla; Pereira, Jéssica; Walter-Nuno, Ana B.; Paiva-Silva, Gabriela O.; Lacerda-Abreu, Marco A.; Meyer-Fernandes, Jose R.; Ramos, Isabela (Frontiers in Physiology, 2023)
Yolk biogenesis and consumption have been well conserved in oviparous animals throughout evolution. Most egg-laying animals store yolk proteins within the oocytes' yolk granules (Ygs). Following fertilization, the Ygs participate in controlled pathways of yolk breakdown to support the developing embryo's anabolic metabolism. While the unfolding of the yolk degradation program is a crucial process for successful development in many species, the molecular mechanisms responsible for yolk mobilization are still mysterious and have mostly not been explored. Here, we investigate the functional role of the oocyte maternally accumulated mRNAs of a protein phosphatase (PP501) and two aspartic proteases (cathepsin-D 405, CD405 and cathepsin-D 352, CD352) in the yolk degradation and reproduction of the insect vector of Chagas disease Rhodnius prolixus. We found that PP501 and CD352 are highly expressed in the vitellogenic ovary when compared to the other organs of the adult insect. Parental RNAi silencing of PP501 resulted in a drastic reduction in oviposition and increased embryo lethality whereas the silencing of CD352 resulted only in a slight decrease in oviposition and embryo viability. To further investigate the PP501-caused high reproduction impairment, we investigated the Ygs biogenesis during oocyte maturation and the activation of the yolk degradation program at early development. We found that the Ygs biogenesis was deficient during oogenesis, as seen by flow cytometry, and that, although the PP501-silenced unviable eggs were fertilized, the Ygs acidification and acid phosphatase activity were affected, culminating in a full impairment of the yolk proteins degradation at early embryogenesis. Altogether we found that PP501 is required for the oocyte maturation and the activation of the yolk degradation, being, therefore, essential for this vector reproduction.